Mercury in fish products: what's the best for consumers between bluefin tuna and yellowfin tuna?. Issue 4 (16th February 2018) - Cammilleri, Gaetano; Vazzana, Mirella; Arizza, Vincenzo; Giunta, Francesca; Vella, Antonio; Lo Dico, Gianluigi; Giaccone, Vita; Giofrè, Salvatore V.; Giangrosso, Giuseppe; Cicero, Nicola; Ferrantelli, Vincenzo
Abstract: A total of 205 bluefin and yellowfin tuna samples were examined for mercury detection in order to verify possible differences and have a detailed risk assessment of the two tuna species. The results showed significant higher mercury concentration in muscle tissue of bluefin tuna respect yellowfin tuna ( p  < 0.001) with mean concentration of 0.84 mg/kg and maximum value of 1.94 mg/kg. These differences can be due the different biological and ecological aspects of the two tuna species and to different oceanographic aspects between Atlantic Ocean and Mediterranean sea. The results obtained in this study suggest an advisable containment of the sources of pollution and further studies on the closed-loop farming of bluefin tuna, in order to ensure the product safety. Abstract :